miR-135a Alleviates Silica-Induced Pulmonary Fibrosis by Targeting NF-κB/Inflammatory Signaling Pathway - Bin Xie; Can Lu; Chen Chen; Jianhua Zhou; Zhenghao Deng (Mediators of Inflammation)
Silica exposure triggers inflammatory response and pulmonary fibrosis that is a severe occupational or environmental lung disease with no effective therapies. The complicated biological and molecular mechanisms underlying silica-induced lung damages have not yet been fully understood. miR-135a inhibits inflammation, apoptosis, and cancer cell proliferation. But the roles of miRNA135a involved in the silica-induced lung damages remain largely unexplored. We investigated the roles and mechanisms of miR-135a underlying silica-induced pulmonary fibrosis. The present study showed silica exposure caused the decrease in miR-135a level but the increase in inflammatory mediators. Transduction of lentivirus expressing miR-135a reduced the level of inflammatory mediators in lung tissues from silica-treated mice and improved pulmonary fibrosis which was consistent with the downregulated α-SMA but enhanced E-cadherin. Moreover, miR-135a overexpression inhibited p-p65 level in lung tissues. Overexpression of miR-135a inhibitor strengthened TLR4 protein level and NF-κB activation in BEAS-2B cells. Injection of PDTC, an inhibitor of NF-κB, further reinforced miR-135a-mediated amelioration of inflammation and pulmonary fibrosis induced by silica. The collective data indicate miR-135a restrains NF-κB activation probably through targeting TLR4 to alleviate silica-induced inflammatory response and pulmonary fibrosis.